Native ants help to spread an invasive African grass in the Cerrado - Rebolo, Isabele F.; Zirondi, Heloiza L. [UNESP]; Fidelis, Alessandra [UNESP]; Christianini, Alexander V. (Wiley, 2022)
Plant–animal interactions may facilitate biological invasions. The African grass Urochloa decumbens is an aggressive invader in the Cerrado. We demonstrate that native ants are dispersing the seeds to short distances, allowing the gradual spread of the invasive to sites without the need of great anthropogenic soil disturbances. Abstract in Portuguese is available with online material.